2019
DOI: 10.1007/s11239-019-01856-3
|View full text |Cite
|
Sign up to set email alerts
|

Increased coagulation factor XIII activity but not genetic variants of coagulation factors is associated with myocardial infarction in young patients

Abstract: The aim of the study was to investigate the possible role of coagulation factor XIII (FXIII) plasma activity and its gene (F13A1) Val34Leu variant as well as thrombospondin-2 gene (THBS2) T/G 3′UTR and thrombospondin-4 gene (THBS4) Ala387Pro variants in the development of myocardial infarction (MI) in young patients. The studied group consisted of 158 patients aged < 50 years with MI, and the control groups consisted of 150 healthy people aged < 50 years and 202 patients suffering from MI aged ≥ 50 years. Fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
(33 reference statements)
3
5
0
4
Order By: Relevance
“…In the current study the allele frequency of FXIII Val34Leu polymorphism was not significantly different between patients and controls. This is consistent with some European studies on premature MI [ 34 , 35 ], but is contrary to others, including a meta-analysis suggesting that it had an unexplained protective role in young MI patients as compared to healthy controls [ 36 – 38 ].…”
Section: Resultssupporting
confidence: 91%
“…In the current study the allele frequency of FXIII Val34Leu polymorphism was not significantly different between patients and controls. This is consistent with some European studies on premature MI [ 34 , 35 ], but is contrary to others, including a meta-analysis suggesting that it had an unexplained protective role in young MI patients as compared to healthy controls [ 36 – 38 ].…”
Section: Resultssupporting
confidence: 91%
“…Abnormal FXIIIa appears to cause thrombotic states such as cardiovascular diseases. 18,49,50 The same abnormal activity has been reported in cancer patients. 17,20 A study in non-small cell lung cancer found that FXIIIa levels in advanced-stage patients are higher than those in healthy controls.…”
Section: Discussionsupporting
confidence: 77%
“…This might represent a missing biochemical link related to clinical observations on the role of FXIII in acute thrombotic events. It has been published that elevated FXIII levels increase the risk of myocardial infarction in young adults and particularly in women [37][38][39]. Reduced fibrinolytic capacity has been defined as a risk factor for myocardial infarction and stroke in young patients, but the exact mechanisms have not been identified as yet [40,41].…”
Section: Discussionmentioning
confidence: 99%